Role of Respiratory Syncytial Virus and Some Bacteria Causes Tonsillitis among Children Under 5 Years Old in Duhok City - Najat Abdeal-Qadir Zaman1, Asma Sumiea Karomi1, Nora Esam Aldeen Mahmood1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Acute infection of the respiratory tract is a prevalent cause of death in children under the age of 5 years, particularly in developing nations. Infection with respiratory syncytial virus is a causative factor for bacterial co-infection with an increase in the incidence of respiratory disease.Objective: This research was intended to clarify the connection between the Respiratory Syncytial Virus RSV and the tonsillitis-causing bacteria.Method: In 120 patients with acute and chronic tonsillitis, swabs were obtained from the tonsils to detect pathogenic and commensal bacteria in the throat, and blood samples collected to identify RSV infection by identifying the antibody value in the serum.The results: Culture results showed that 78.53% of the bacteria isolated belonged to the Gram-positive group and that only 21.47% belonged to the Gram-negative group, (51.98%) were positive for pathogenic bacteria while (48.02%) were positive for commensal bacteria and showed the highest rate of pathogenic bacteria isolated from tonsillitis patients was to Staph. aureus and Strep. pyogenes. Serological testing using ELISA showed that respiratory syncytial virus infection increases tonsillitis co-infection. Type of antibodies showed a change depending on the sex group and the stages of immune response maturity.